Why Muslim women and smartphones - Waltorp, Karen, author.
1 online resource (200 pages)
Keywords: Using an assemblage approach to study how Muslim women in Norrebro, Denmark use their phones, Karen Waltorp examines how social media complicates the divide between public and private in relation to a group of people who find this distinction of utmost significance. Building on years of ethnographic fieldwork, Waltorp's ethnography reflects the trust and creativity of her relationships with these women which in turn open up nuanced discussions about both the subject at hand and best practice in conducting anthropological research. Combining rich ethnography with theoretical contextualization, Waltorp's book alternates between ethnography and analysis to illuminate a thoroughly modern community, and reveals the capacity of image-making technology to function as an infrastructure for seeing, thinking and engaging in fieldwork as an anthropologists. Waltorp identifies a series of important issues around anthropological approaches to new media, contributing to new debates around the anthropology of automation, data and self-tracking.